A força do trabalho feminino na Odontologia, em Araçatuba - SP - Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP]; Blanco, Mikaela Reginee Basso [UNESP] (Faculdade De Odontologia De Bauru - USP, 2003)
A process of femininity has been recently occurring in the professions, mainly in the health field. In this study, the authors aimed at analyzing the dental practice by women as regards the income, degree of satisfaction and problems they have been facing. One hundred female dentists from Araçatuba, SP, were interviewed and answered a questionnaire designed for that purpose, which contained thirty questions. The results showed that 87% are not the main source of income of the family. Among the interviewed, 38% have an income below R$ 1500; 44% agreed that the income from dental practice is not enough. From all, 78% considered themselves as satisfied with the profession, however 58.2% would not stimulate their children to pursue the dental career. The main complains are the low income and saturation of the profession. Concerning health, 50.5% have some professional diseases, mainly backache and varicose veins. It was concluded that, even though most subjects stated to be satisfied with the profession, aspects such as financial and health problems, complains and no recommendation of this career for their children demonstrate their sometimes unconscious dissatisfaction with the dental practice.

Nos últimos anos tem havido um processo de feminilização nas profissões, principalmente na área da saúde. Nesse trabalho, o objetivo foi analisar o exercício da odontologia por profissionais do sexo feminino, quanto à renda mensal obtida com a profissão, ao grau de satisfação e problemas enfrentados, dentre outros aspectos. Foram entrevistadas 100 cirurgiãs-dentistas, da cidade de Araçatuba, SP, utilizando-se um formulário com 30 perguntas. Os resultados mostraram que 87% disseram não ser a principal fonte de renda de sua família, 38% possuem renda mensal inferior à R$1.500,00; 44% afirmaram que a renda obtida com o exercício profissional não é suficiente. Do total, 78% consideram-se satisfeitas com a profissão, porém 58,2% não incentivariam seus filhos a cursarem odontologia. As principais queixas apontadas são: a baixa remuneração que a profissão lhes proporciona e a saturação do mercado de trabalho. Quanto à saúde, 50,5% possuem algum problema relacionado à atuação profissional, principalmente dores na coluna e varizes. Conclui-se que embora a maioria das entrevistadas afirmou estar satisfeita com a profissão, os problemas financeiros, de saúde, as queixas e a não recomendação da profissão para o filho, traduzem a insatisfação, às vezes inconsciente, das mulheres no exercício da odontologia.
The women workforce in Dentistry in Araçatuba - SP
Keywords: Women working; Women health; Dental education; Trabalho feminino; Saúde da mulher; Educação em odontologia